Characterization of the Angle, Delay and Polarization of Multipath Signals for Indoor Environments - Gurrieri, Luis E.; Willink, T.; Petosa, A.; Noghanian, S. (Université d'Ottawa | University of Ottawa, 2008)
A high-resolution channel sounding technique has been used to investigate the cross-polarization of electromagnetic waves in the 5-6 GHz band. Experiments were performed in two non-line-of-sight indoor locations, and it was found that there is a strong dependency of the cross-polarization of multipath components on the elevation angle-of-arrival. For a vertically polarized transmitting antenna, clusters of co-polarized multipath components were confined predominantly to the region around the horizontal plane that contains the virtual line-of-sight between transmitter and receiver. In contrast, cross-polarized signals were detected for a variety of elevation angles with considerable power levels. The surroundings of the receiver were identified as the principal source of depolarized signals. In addition, time dispersion analysis of the multipath signals led to the determination of the AoAs where there is a strong correspondence between co- and cross-polarized signals as a consequence of the partial depolarization of MPCs. This work supports the exploitation of the joint space and polarization diversities in indoor propagation scenarios to improve the system performance.
Keywords: polarization; delay; angle; angle-of-arrival; time-of-arrival; direction-of-arrival; channel capacity; cross-polarization; channel sounding; Electric field measurement; patch antennas; transmitters; receivers; polarization diversity; multipath channels; indoor communication; electromagnetic wave propagation; direction-of-arrival estimation